2006
DOI: 10.1016/j.cardiores.2005.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease1/redox factor-1 inhibits monocyte adhesion in endothelial cells

Abstract: These data provide evidence that APE1/ref-1 in endothelial cells mitigates TNF-alpha-induced monocyte adhesion and expression of vascular cell adhesion molecules, and this anti-adhesive property of APE1/ref-1 is primarily mediated by a NOS-dependent mechanism. Furthermore, APE1/ref-1 may inhibit VCAM-1 expression by inhibiting superoxide production and p38 MAPK activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…It is well known that mitogen-activated protein kinase (MAPK)s are activated by growth factors, environmental stresses and inflammatory cytokine (Chen et al, 2001). We previously reported that the overexpression of APE1/Ref-1 using the adenoviral gene transfer system inhibits TNF-α-induced ROS production and VCAM-1 in endothelial cells (Angkeow et al, 2002;Kim et al, 2006;Lee et al, 2009). In addition, p38 MAPK activation by TNF-α was blocked by overexpression of APE1/Ref-1 resulting in inhibition of TNF-α-induced VCAM-1 in endothelial cell .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that mitogen-activated protein kinase (MAPK)s are activated by growth factors, environmental stresses and inflammatory cytokine (Chen et al, 2001). We previously reported that the overexpression of APE1/Ref-1 using the adenoviral gene transfer system inhibits TNF-α-induced ROS production and VCAM-1 in endothelial cells (Angkeow et al, 2002;Kim et al, 2006;Lee et al, 2009). In addition, p38 MAPK activation by TNF-α was blocked by overexpression of APE1/Ref-1 resulting in inhibition of TNF-α-induced VCAM-1 in endothelial cell .…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme is particularly important under limited glutathione content conditions, such as obtain in lead (Pb)-exposed animals (Hsu, 1981;Hunaiti et al, 1995), and plays a significant role in the development of tolerance to oxidative stress in the adaptive responses of cells (Wassmann et al, 2004 (Grosch et al, 1998;Silber et al, 2002). Conversely, overexpression of Ref-1 repair functions stimulates an increase in resistance to certain alkylating agents and oxidative stresses (Tomicic et al, 1997;Grosch et al, 1998;Kim et al, 2006;Lee et al, 2009). Ref-1 and p53 proteins are required for selenium protection from DNA damage in the human and mouse fibroblasts (Fischer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular superoxide and hydrogen peroxide production were detected using the superoxide-sensitive fluorophore dihydroethidine (DHE) and the peroxide-sensitive fluorophore 2',7'-dichlorodihydrofluorescein diacetate (DCF-DA) as described previously (Angkeow et al, 2002;Kim et al, 2006). In order to detect DHE or DCF-DA fluorescence, the cells were cultivated in chamber slides (2×10 5 cells/well) (Nalge Nunc International).…”
Section: Detection Of Superoxide and Hydrogen Peroxide Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantitative adhesion assay, U937 cells were fluorescently labeled with 2',7'-bis-(2-carboxyethyl)-5-(and-6)-carboxy-fluorescein acetoxymethyl ester (BCECF-AM) by incubating the cells (1×10 7 cells/ml) with 1 µmol/L BCECF-AM in RPMI-1640 medium for 30 min at 37 o C and 5% CO 2 as previously described [10][11][12] . HUVECs were seeded in 24-well plates to reach confluent monolayer and pretreated with KRGE for 24 hours in EGM-2 medium.…”
Section: Monocyte Adhesion Assaymentioning
confidence: 99%